Development and polymorphism of simple sequence repeat (ssr) dna markers for Duabanga moluccane blume - Liew, Kit Siong (Universiti Malaysia Sarawak, (UNIMAS), 2012)
Duabanga moluccana Blume (or locally known as Sawih) is an indigenous fast growing tree species that has been selected for planted forest development in Sarawak. It possesses great commercial values in production of various wood products. Therefore, the development of an array of simple sequences repeats (SSRs) or micro satellite DNA based-markers is absolutely necessary to study the genetic makeup of this species. These molecular markers had been rapidly used in the selection of plus trees, quality control in seed production, investigation of population genetics and conservation management. Isolation of high-quality genomic DNA from D. moluccana is vital for molecular marker development as well as other downstream application) In the present study, an improved method of total DNA isolation from D. moiuccana was established. These modifications include: 1) precipitating DNA with '/3 volwne of 5 M NaCI together with isopropanol; 2) using I% ~-mercaptoethanol in the extraction buffer; 3) sample incubation time of 40 minutes at 65 DC, and 4) adding a CIA extraction step. By using this method, the isolated DNA was suitable for amplification and restriction digestion analysis. In this study, we used ISSR-suppression method to develop simple sequence repeats (SSRs) markers for D. moiuccana. Overall, 44 SSR regions were identified. The microsatellite motifs contained simple perfect and simple imperfect microsatellites constituted by di-and trinucleotides and, perfect/imperfect compounds. The most nwnerous class was the perfect compound with 24 (54.5%) occurrences, followed by the imperfect compounds with 8 (18.2%), simple perfect with 8 (18.2%), and the simple imperfect repeats with 4 (9.1 %). Majority of the dinucleotide microsatellites found in the Sawih genome was AG/GA/CT/TC repeats (83.3%) followed by ACICAITG/GT repeats (16.7%). Primer pairs were designed for 43 SSR regions. The newly identified SSR markers were characterized by screening DNA templates from 20 individuals of D. moluccana seedlings. Among 43 primer pairs, 25 (58.1 %) SSR markers amplified the expected fragments size while 17 (39.5%) produced unexpected PCR products or multiple bands. One primer did not generate amplification products in most of the Sawih samples. A total of 115 alleles were detected across 25 loci analysed. The number of alleles per locus ranged from 2 to 8, with a mean value of 4.60. Polymorphism Information Content (PIC) values ranged from 0.225 to 0.792, with an average of 0.604. A success rate of transferability of D. moluccana microsatellite markers varied, ranging from 84% in Duabanga grand~flora, 36% in Neolamarckia cadamba, 24% in Canarium odontophyllum and 28% in Shorea parvifolia. The development of an array of microsatellite markers herein could be applied to generate useful baseline genetic information for effective selection of plus trees, provenance trials, and establislunent of forest seed production areas (SPAs) of D. moluccana in the selected forest reserves for tree plantation and improvement activities. Besides, the transferability of the newly developed microsatellites markers across a range of species and genera suggests their potential usefulness for a variety of population genetic studies.